Cell surface expression of the env gene polyprotein of dual-tropic mink cell focus-forming murine leukemia virus. - Famulari, N G (1979)
Differences have been observed in the kinetics of processing of the env gene polyprotein of ecotropic, xenotropic, and dual-tropic mink cell focus-forming (MCF) murine leukemia virus. In pulse-chase experiments, the env gene polyprotein of the dural-tropic MCF virus exhibits a marked increase in stability relative to that of either ecotropic or xenotropic virus. A comparison of cell surface expression of env gene products of ecotropic, xenotropic, and dual-tropic MCF murine leukemia virus has been made. Only gp70 is accessible to lactoperoxidase-catalyzed radioiodination of fibroblasts infected by ecotropic or xenotropic virus, whereas both gp70 and the env gene polyprotein are expressed on the surface of dual-tropic MCF virus-infected cells.